'China-focused' human resource management? A critical analysis of a decade of journal-published research, 2008–2017. Issue 5 (20th October 2017) - Busse, Ronald
Abstract: This article seeks to provide reliable insights into current trends of 'China-focused' Human Resource Management (HRM) vis-à-vis the need for a more 'contextualized' framework. It tries to capture the status quo of the literature in the field – in terms of evaluating quality indicators (such as citation rates), author information (such as affiliations), methodological data (such as sample foci) and content-related facts (such as subject matters), amongst others. Ten SSCI-indexed journals were systematically selected for the study, as they explicitly focus on HRM and/or on Asian management issues. The findings are based on an in-depth analysis of 159 articles published between 2008 and 2017. A rich content analysis is presented to illustrate current trends. Although the results have to be treated with caution, I provide some evidence for what numerous scholars recently point out may be the case for the field of China-focused HRM: A contextual and methodological narrowing. It is hoped that the present article may add to the debate on the future of the field.